Low-damping ferromagnetic resonance in electron-beam patterned, high-Q vanadium tetracyanoethylene magnon cavities - Andrew Franson; Na Zhu; Seth Kurfman; Michael Chilcote; Denis R. Candido; Kristen S. Buchanan; Michael E. Flatté; Hong X. Tang; Ezekiel Johnston-Halperin (APL Materials, 2019)
Integrating patterned, low-loss magnetic materials into microwave devices and circuits presents many challenges due to the specific conditions that are required to grow ferrite materials, driving the need for flip-chip and other indirect fabrication techniques. The low-loss (α = (3.98 ± 0.22) × 10−5), room-temperature ferrimagnetic coordination compound vanadium tetracyanoethylene (V[TCNE]x) is a promising new material for these applications that is potentially compatible with semiconductor processing. Here, we present the deposition, patterning, and characterization of V[TCNE]x thin films with lateral dimensions ranging from 1 μm to several millimeters. We employ electron-beam lithography and liftoff using an aluminum encapsulated poly(methyl methacrylate), poly(methyl methacrylate-methacrylic acid) copolymer bilayer [PMMA/P(MMA-MAA)] on sapphire and silicon. This process can be trivially extended to other common semiconductor substrates. Films patterned via this method maintain low-loss characteristics down to 25 μm with only a factor of 2 increase down to 5 μm. A rich structure of thickness and radially confined spin-wave modes reveals the quality of the patterned films. Further fitting, simulation, and analytic analysis provide an exchange stiffness, Aex = (2.2 ± 0.5) × 10−10erg/cm, as well as insights into the mode character and surface-spin pinning. Below a micron, the deposition is nonconformal, which leads to interesting and potentially useful changes in morphology. This work establishes the versatility of V[TCNE]x for applications requiring highly coherent magnetic excitations ranging from microwave communication to quantum information.